THE RELATIONSHIP BETWEEN RELIGIOSITY AND SELF EFFICACY WITH ANXIETY IN FACING THESIS EXAMS IN FINAL SEMESTER STUDENTS OF ISLAMIC GUIDANCE AND COUNSELING STUDY PROGRAM, KH MUKHTAR SYAFAAT UNIVERSITY - Karim, Abdul; Nurrohmah, Ain (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
This researcher examined the relationship between religiosity and self- efficacy and anxiety about facing thesis exams in final semester students of the Islamic Guidance and Counseling Study Program at KH Mukhtar Syafaat University. This research was motivated by students' anxiety in facing the thesis exam. One of the factors that influence student anxiety is religiosity and self-efficacy. The aim of this research is to find out how religiosity is related to anxiety about facing the thesis exam. To be able to find out how religiosity and self-efficacy are related to anxiety facing the thesis exam. This research uses quantitative research methods. Quantitative research emphasizes analysis of numerical data processed using statistical methods. The method used in this research is the correlational method. Data was collected through questionnaire techniques, with different data collection strategies for two groups of respondents: using Google Forms for respondents who were not in the boarding school and offline questionnaires for respondents who were in the boarding school. The results obtained in this research are the correlation coefficient value of 0.478 contained in the table, it can be concluded that there is a positive relationship between religiosity and anxiety. This means that if a person's level of religiosity increases, it is likely that their level of anxiety will also increase, and vice versa. The positive correlation coefficient value of 0.679 concludes that there is a strong positive relationship between self-efficacy and anxiety. This means that if a person's level of self-efficacy increases, it is likely that their level of anxiety will also increase, and vice versa. The correlation coefficient value between X1 (religiosity) and X2 (self efficacy) with Y (anxiety) is 0.695. This value is positive, which indicates that there is a positive relationship between religiosity and self-efficacy on anxiety levels. This means that if the religiosity value increases, anxiety also tends to increase, as does self-efficacy. Overall, religiosity, self-efficacy, and anxiety have a unidirectional relationship. The correlation coefficient value of 0.695 is included in the strong category according to the r value interpretation table, which is between 0.600 to 0.799.